A DETAILED OVERVIEW OF MEDICINAL PLANTS HAVING HYPOGLYCEMIC ACTIVITY - Sandra Celine; Shawn Tomy; Ujwala TK; Sam Johnson Udaya Chander (International Journal of Phytomedicine, 2016)
Diabetes mellitus represents a spectrum of metabolic disorder, which has become one of the major public health concerns worldwide. Diabetes mellitus has emerged as a third leading killer after cancer and cardiovascular/cerebrovascular diseases and India has a distinction of having largest number of diabetics in world second to China. Herbal medicine for treating chronic diseases, especially diabetes has gained an exponential growth in the last few years and both developing and developed countries are adopting herbal drugs for treatment of diabetes mellitus. The World Health Organization (WHO) has listed 21,000 plants, which are used for medicinal purposes around the world. The WHO has defined herbal medicines as finished labelled medicinal products that contain aerial or underground parts of the plants or other plant material or combination thereof as active ingredients, whether in crude state or as plant preparations. This review attempts to present the profiles of plants with hypoglycemic properties, reported in the literature with proper categorization according to the botanical name, family, parts used, chemical constituents, and its other uses. Relevant medical databases and websites were searched. To qualify for inclusion, the herbs should have confirmed hypoglycemic potential. Other criteria for inclusion are: published in English and peer-reviewed journals. We also used related keywords like diabetes mellitus, plant, herb, glycemic control, natural or herbal medicine, Ayurvedic plants, and hypoglycemic plants, as keywords or combination of them. A total of 151 herbs belonging to 72 families were outlined in this review.